Further studies on assessing ductile fracture using continuous damage coupled to an elasto-plastic material model - Vaz Jr. M.* (2005)
In recent years, failure assessment of metal forming operations using numerical simulation has been gaining momentum due to the rapid development of computational techniques for elasto-plastic problems. Furthermore, the recent proposals for numerical evaluation of ductile fracture has also potential for further improvement in tool design by means of reduction of forming defects. The present work aims at discussing possible improvements of the damage equation to better accommodate the transition from tensile to compressive stress states. Aspects of ductile failure are also presented.